2022
DOI: 10.3390/antiox11061114
|View full text |Cite
|
Sign up to set email alerts
|

A Multifactorial Regulation of Glutathione Metabolism behind Salt Tolerance in Rice

Abstract: Knowledge of the stress-induced metabolic alterations in tolerant and sensitive plants is pivotal for identifying interesting traits that improve plant resilience toward unfavorable environmental conditions. This represents a hot topic area of plant science, particularly for crops, due to its implication in food security. Two rice varieties showing dissimilar resistance to salt, Baldo and Vialone Nano, have been studied to investigate the mechanisms underpinning tolerance toward salinity, and these studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…In summary, GST can actively respond to salt stress. Previous studies have confirmed the important role of GST in improving salt tolerance in plants such as rice [12], garlic [13], and tomato [14] in vivo. However, there have been no reports on the mechanism of how GST plays a role in cucumber growth and reducing salt-alkali damage.…”
Section: Introductionmentioning
confidence: 79%
“…In summary, GST can actively respond to salt stress. Previous studies have confirmed the important role of GST in improving salt tolerance in plants such as rice [12], garlic [13], and tomato [14] in vivo. However, there have been no reports on the mechanism of how GST plays a role in cucumber growth and reducing salt-alkali damage.…”
Section: Introductionmentioning
confidence: 79%
“…In plants, an initial stress response is generally related to glutathione metabolism. Reduced glutathione (GSH) acts as a redox buffer to maintain the intracellular reduction status [ 36 ]. The AsA–GSH cycle is indispensable in eliminating H 2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione acts as an antioxidative substrate by conjugating with toxic electrophilic compounds, scavenging free radicals, and reducing peroxides [ 52 , 53 ]. For example, a salt-tolerant rice variety has a higher glutathione content than a salt-sensitive variety [ 36 ]. In plants exposed to salt stress, the glutathione redox state is disturbed and GSH is oxidized to GSSG [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…NaCl stress adversely affects plants by inducing osmotic stress, ion toxicity, nutritional imbalance, and oxidative stress, which can retard plant growth and even cause death [45][46][47]. In addition, excessive accumulation of ROS is a secondary stress that further impairs plant performance [48].…”
Section: Discussionmentioning
confidence: 99%